Political Law Regulation of Judicial Institutions in Exercising the Powers of an Independent Judgment: Before and After Amendments to the 1945 Constitution - Pakaya, Salahudin; Nalali , Adrianto (International Journal Papier Public Review, 2020)
The Supreme Court is a judicial institution that has existed since the Indonesian state was formed in 1945. This institution was formed based on the mandate of the constitution in article 24 of the 1945 Constitution, namely "judicial power is exercised by a Supreme Court and other judicial bodies according to law". But in fact, in the course of Indonesia's national and state life from its independence in 1945 to 1998, the judicial power exercised by the Supreme Court was not free and independent, both institutionally and independently of its judges. The influence of the executive power held by the president on the judicial power exercised by the Supreme Court can actually be observed in the politics of regulating judicial power through laws by the executive and legislative bodies during the old order government (President Soakarno 1945-1966) and the new order (President Soeharto 1967-1998). The judicial power law that was formed has actually subordinated the judiciary under the power of the president. This is the result of efforts to form the state of Indonesia as a country based on kinship that does not adhere to a separation of powers (executive, legislative and judicial) as the trias politica concept put forward by John Locke and Montesquie. With the 1998 reforms which in turn succeeded in amending the 1945 Constitution in order to realize the Indonesian state as a democratic legal state, the judiciary has been strengthened as an institution that is truly free and independent from the influence of extra-judicial powers.